In-situ direct grafting of graphene quantum dots onto carbon fibre by low temperature chemical synthesis for high performance flexible fabric supercapacitor. (March 2017) - Islam, Mohammad S.; Deng, Yan; Tong, Liyong; Roy, Anup K.; Faisal, Shaikh N.; Hassan, Mahbub; Minett, Andrew I.; Gomes, Vincent G.
Abstract: A novel chemical synthesis method has been developed to directly graft graphene quantum dots (GQDs) onto carbon fibre (CF) in-situ via covalent ester linkages at low temperature (90 °C). SEM and TEM images depict the grafting of GQDs on CF showing about 75% of the GQD falls below 40 nm. The grafting was further confirmed by FTIR, RAMAN, XPS and XRD spectroscopy. The flexible fabric supercapacitor manufactured using the grafted materials shows increased electrochemical capacitance (about 5.5 times) than that of CF by providing active surface sites of GQDs, creating defects on the surface and preventing GQD recombination. This supercapacitor maintained approximately 97% of its initial capacitance after 5000 cycles at 2 A g −1 current density, suggesting a stable performance of the supercapacitor and holds a promising potential in the field of advanced flexible electronic devices.